THE ROLE OF TEACHERS IN SHAPING STUDENTS' MORALS IN THE ERA OF MODERNIZATION AND DIGITALIZATION OF EDUCATION - Nurhasan, Nurhasan; Nurhasanah, Nurhasanah (Tahdzib Al-Akhlaq: Jurnal Pendidikan Islam, 2025)
Education in this modern era is not enough if it only emphasizes mastery of various scientific and technological disciplines. The formation of student character is actually much more important so that students are able to face various challenges in global life with noble moral values ​​and strong character. Basically, a teacher has a strategic role in forming strong morals and character through role models, habits, and fostering positive values ​​in the school environment. This study aims to describe the role of teachers in the formation of student character in modern schools oriented towards technology and creativity. The method used is descriptive qualitative through literature studies and observations at Muhammadiyyah 2 Senior High School Jakarta, Jl. Garuda no. 33, Central Jakarta. The results show that a teacher is a central figure in instilling the values ​​of responsibility, discipline, cooperation, and integrity. However, challenges arise from the influence of digital media and shifts in social values ​​among students. Strengthening teachers' social-emotional competencies, collaboration with parents, and integration of character education into the curriculum are needed so that the formation of student character can take place effectively and sustainably both in school and outside of school